2019
DOI: 10.3390/molecules24010191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Potential of Some Novel Benzimidazole-1,3,4-Oxadiazole Compounds

Abstract: Discovery of novel anticandidal agents with clarified mechanisms of action, could be a rationalist approach against diverse pathogenic fungal strains due to the rise of resistance to existing drugs. In support to this hypothesis, in this paper, a series of benzimidazole-oxadiazole compounds were synthesized and subjected to antifungal activity evaluation. In vitro activity assays indicated that some of the compounds exhibited moderate to potent antifungal activities against tested Candida species when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 56 publications
0
23
0
2
Order By: Relevance
“…The syntheses of the target compounds 3a – p were realized as summarized in Scheme 1 . Known triazoles 1a – d were synthesized according to our already published method [ 33 , 34 ]. The S -alkylation of the triazole ring of compounds 1a – d with an appropriate 2-bromoacetophenone moiety 2a – d using potassium carbonate as base generated the target derivatives 3a – p .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The syntheses of the target compounds 3a – p were realized as summarized in Scheme 1 . Known triazoles 1a – d were synthesized according to our already published method [ 33 , 34 ]. The S -alkylation of the triazole ring of compounds 1a – d with an appropriate 2-bromoacetophenone moiety 2a – d using potassium carbonate as base generated the target derivatives 3a – p .…”
Section: Resultsmentioning
confidence: 99%
“…The mixture was cooled and poured into iced-water. The obtained solid was filtered, washed with water, dried and recrystallized from ethanol [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it is absent in humans, that can contribute with the development of selective drugs against pathogens [ 25 ]. 1,3,4-oxadiazole-based drugs have been widely studied by researchers [ 21 , 22 , 23 , 26 , 27 , 28 , 29 ]. These compounds have a high therapeutic power and broad spectrum of action, such as anticancer, antifungal, antibacterial, antitubercular, anti-inflammatory, antineuropathic, antihypertensive, antihistaminic, antiparasitic, antiobesity, antiviral activity, among others [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro antifungal activity of all derivatives (4a-4j) was evaluated against C. albicans (ATCC 90030), C. glabrata (ATCC 90030), C. krusei (ATCC 6258) ve C. parapsilopsis (ATCC 22019) at concentrations between 1 mg/mL-1.95 μg/mL. Activity studies were conducted following EUCAST protocol in accordance with previous studies reported by our research group (Karaburun et al 2018, Karaburun et al 2019).…”
Section: Antifungal Activitymentioning
confidence: 99%